Evaluation of the efficacy of Centella asiatica 5% alcoholic extract ointment in thermal trauma in mice - Despina F. Georgiana Oprea; Diana Brezovan; Florin Muselin; Alexandru O. Doma; Mihai Folescu; Sergiu A. Alic Orășan; Romeo T. Cristina; Eugenia Dumitrescu (Medicamentul Veterinar)
Centella asiatica or Brahmi~Gotu Kola is a plant used since ancient times as a medicinal plant in countries such as India, Nepal, China, Sri Lanka, and Madagascar. The plant is considered to be one of the most useful plants for revitalizing nerve cells, which is why in India it is known as the "brain plant" or used to treat skin conditions and heal wounds. The plant is still often used in two traditional branches of Indian medicine, Ayurveda and Unani. The aim of this study was to evaluate the efficacy of Centella asiatica extract ointment in thermally injured mice. This study was performed on a total of 12 Balb/c mice aged 24-26 weeks, which were divided into two groups: one experimental and one control. The duration of the experiment was 14 days, with collections of biological material on days 3, 7, and 14 of the experiment. In the case of the tested ointment, clinical healing occurred after the 9th day of treatment by debridement of the formed crust and highlighting a regeneration epithelium